Liderazgo transformacional del director y su relación con el clima organizacional en la Institución Educativa Colegio Aplicación Unap, Iquitos – 2017 - Moreno Torres, Rocio Datnia (2024)
The purpose of the research is to show the correlation that exists between the variables Transformational Leadership with the Organizational Climate variable, in the teachers of the Educational Institution of the UNAP Application, for them the general objective was to analyze the relationship that exists between the Transformational Leadership of the Director and the Organizational Climate according to the perception of the teachers of the Educational Institution College Application UNAP. The methodology; the type of non-experimental research, the correlational design, was worked with a sample of 38 teachers from the UNAP Application school. We used Spearman's Chi square and r, with a level of significance X2 calcified = 4.87 p = 0.027 X2tabular = 3.84 and gl = 1 Spearman correlation r = 0.358, the result is that there is a deficient relationship between the Transformational Leadership of the Director and the Organizational Climate, according to the perception of the teachers of the UNAP Application College.